2012
DOI: 10.1189/jlb.0711336
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis vacuole maturation in infected macrophages

Abstract: Macrophages can suppress Chlamydia replication by targeting the bacteria to degradative organelles such as lysosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 50 publications
(58 reference statements)
4
39
0
Order By: Relevance
“…Material that reacted with Chla- Fields et al mydia-specific antibodies was routinely detected in dispersed, punctate patterns in control BV2 cells, whereas mature inclusions were rarely observed. This pattern is consistent with a previous report indicating killing of chlamydiae in macrophages via autophagy (12). In contrast, treatment of cells with perforin-2 siRNA resulted in the routine detection of apparently intact, mature chlamydial inclusions.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Material that reacted with Chla- Fields et al mydia-specific antibodies was routinely detected in dispersed, punctate patterns in control BV2 cells, whereas mature inclusions were rarely observed. This pattern is consistent with a previous report indicating killing of chlamydiae in macrophages via autophagy (12). In contrast, treatment of cells with perforin-2 siRNA resulted in the routine detection of apparently intact, mature chlamydial inclusions.…”
Section: Resultssupporting
confidence: 81%
“…Multiple reports have documented the ability of professional phagocytes to directly kill intracellular chlamydiae (12,14,18). Given the constitutive expression of Mpeg1/perforin-2 in macrophages (15) and the role of perforin-2 in limiting intracellular bacterial replication (17), we questioned whether perforin-2 might contribute to the limitation of chlamydial growth in macrophages.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, unlike epithelial cells, M are not a hospitable niche for chlamydial intracellular replication, as illustrated by the fact that compared to the case in epithelial cells, only a small fraction of chlamydial RBs are detected in M (49). C. trachomatis destruction inside M has been associated with host cell autophagy, a process by which cells degrade cytoplasmic proteins and organelles (49)(50)(51). Also, studies have demonstrated that M autophagy can enhance antigen presentation to T cells (52).…”
mentioning
confidence: 99%